(untitled) (The Review of Diabetic Studies, 2025)
Background: Transfusion reactions continue to pose a major challenge to patient safety and are frequently linked to preventable errors across the transfusion process. Effective prevention increasingly relies on interprofessional collaboration, particularly among nursing, blood bank laboratory, and pharmacy teams, who collectively oversee patient assessment, component preparation, medication management, and post-transfusion monitoring. Objective: To systematically review the evidence on how interprofessional vigilance led by nursing, blood bank laboratory, and pharmacy teams contributes to preventing transfusion reactions and improving transfusion safety. Methods: A systematic search was conducted in PubMed, Scopus, Web of Science, and CINAHL for studies published between 2000 and 2024. Eligible studies evaluated collaborative interventions, communication strategies, or team-based protocols aimed at minimizing transfusion-related complications. Data were extracted and synthesized narratively with emphasis on multidisciplinary roles, safety outcomes, and process improvements. Results: Across the included studies, interprofessional teamwork significantly reduced the incidence of transfusion reactions through improved patient identification, enhanced compatibility verification, precise blood component handling, and vigilant monitoring. Nursing played a central frontline role in surveillance and early recognition of adverse events, while laboratory teams ensured accuracy in testing and crossmatching. Pharmacy involvement improved medication–transfusion safety, particularly in mitigating drug–blood product interactions. Interprofessional education, shared checklists, and standardized communication tools further strengthened adherence to transfusion safety protocols. Conclusion: Preventing transfusion reactions requires coordinated, evidence-based collaboration across nursing, laboratory, and pharmacy teams. Enhanced communication, shared responsibilities, and continuous training significantly improve transfusion safety and patient outcomes. Health systems should integrate structured interprofessional practices to minimize preventable transfusion-related complications.